Boundary value problems of fractional differential equations with nonlocal and integral boundary conditions - Essel, John Fiifi; Zhang, Lingling; Addai, Emmanuel (International Journal of Advanced Engineering Research and Science, 2021)
The boundary value problems of fractional differential equations involving Caputo derivatives are examined in this article. The ultimate goal of our study is to institute the existence and uniqueness properties for our boundary problems with nonlocal and integral boundary conditions by applying the Banach and the Schaefer’s theorems of fixed point. We finally discuss two applicable questions to enhance the comprehension of our outcomes and conclude by summarizing our results and giving vital suggestions for further research works in relation to our study.